Comparison of the tourism in Vienna and Budapest - Hlatká, Adéla (2014)
This thesis deals with tourism in Vienna and in Budapest. The aim of the thesis is to find similarities and differences between tourism in these two cities. First of all types of tourism dominant in these cities are described. The following chapters analyzes information and data regarding these metropolises. Focus is given to realization and localization presumptions of tourism. Collected data are compared and finally SWOT analysis are made to evaluate tourism in Vienna and in Budapest and to find ways that could improve position of these capitals on tourism market.